Long-term performance improvement in youth training - Pollany, W.
This presentation will not focus on physical factors but on the development of the most important psychological prerequisites for high level performance in game sports, the ability to pick up information and with that execute the best possible reaction in terms of efficiency. The main point in this context is the decision making. The author shows by this schedule that teaching and training of decision making is a very complex process and it will take a lot of time and patience to have it done properly. Therefore he always wonders that so little interest is paid into that essential item of game behaviour and a lot of coaches do not work on it at all but take it more or less for given or not given in some player. Again he stresses that decision making is a skill and therefore can be trained and improved.